Descriptions of the Messianic Era in Jewish Averroist Thought: Between Anti-Zionism, Political Zionism and Practical Zionism - Sadik, Shalom (Jewish Thought, 2023)
The purpose of this article is to analyze the various approaches regarding the days of the Messiah and the way to achieve them among the Jewish medieval Averroists. As it appears, three different opinions can be identified. Rabbi Levi ben Abraham describes a position like that of Maimonides, according to which the path to redemption involves successful wars. This position is similar to the practical Zionism of the early twentieth century. In contrast, Rabbi Yosef ben Kaspi and Rabbi Nissim of Marseille prefer the diplomatic path, by which the Jews will receive permission from the nations to settle in Israel – a phenomenon like the decree of Cyrus after the destruction of the First Temple. Contrary to these two positions, in the view of Rabbi Yitzchak Polqar, the return to the land and the political domain is morally wrong and invalid. In his esoteric view, the situation of the Jews in exile is preferable, as they do not need to engage in the moral transgressions associated with governing a state; therefore, in his opinion, the pinnacle of success will be a relatively peaceful situation as a small minority in exile.